Catheter Directed Thrombolysis for Not Immediately Threatening Acute Limb Ischaemia: Systematic Review and Meta-Analysis. (April 2023) - Doelare, Sabrina A.N.; Koedam, Thomas W.A.; Ebben, Harm P.; Tournoij, Erik; Hoksbergen, Arjan W.J.; Yeung, Kak K.; Jongkind, Vincent; ,; Acosta, S.; Grip, O.; Kashyap, V.S.; Vakhitov, D.
Abstract : Objective: This systematic review and meta-analysis reports the outcomes of catheter directed thrombolysis (CDT) in patients with not immediately threatening (Rutherford I) acute lower limb ischaemia (ALI). Data Sources: PubMed, Embase, and the Cochrane Library. Review Methods: A systematic search of PubMed, Embase, and the Cochrane Library was performed to identify observational studies and trials published between 1990 and 2022 reporting on the results of CDT in patients with Rutherford I ALI. A meta-analysis was performed using a random effects model with 95% confidence intervals (CIs). The outcomes of interests were treatment duration, angiographic success, bleeding complications, amputation and mortality rates, primary and secondary patency, and functional outcome expressed as pain free walking distance. Results: Thirty-nine studies were included, comprising 1 861 patients who received CDT for not immediately threatening ALI. Funnel plots showed an indication of publication bias, and heterogeneity was substantial. Data from 5 to 13 studies were included in the meta-analysis. The pooled treatment duration was 2 days (95% CI 1 – 2), with an angiographic success rate of 80% (95% CI 73 – 86) and a 30 day freedom of amputation rate of 98% (95% CI 92 – 100). The major bleeding rate was 5% (95% CI 2 – 14), with a 30 day mortality rate of 3% (95% CI 1 – 5). The amputation free survival rate was 71% (95% CI 62 – 80) at the one year and 63% (95% CI 51 – 73) at the three year follow up. Long term patency rates were retrieved from four studies: 48% at one year (95% CI 27 – 70). No data could be retrieved on patient walking distance. Conclusion: Although CDT in the treatment of not immediately threatening ALI showed high angiographic success, the long term outcomes were relatively poor, with low patency and a substantial risk of major amputation. Further research is required to interpret the outcome of CDT in the context of potential confounders such as age and comorbidities.